The awareness of the citizens of Swietokrzyskie Voivodeship on the genetic predisposition on cancer - Wojarska, Izabela Kamila (Journal of Education, Health and Sport, 2017)
Introduction: Cancers are the major concern of the modern world, they are in fact the fourth most common cause of death in the world and second in developed countries. The root cause of tumour development lies in genetics. In the last few years a significant rise in the molecular genetics and laboratory studies, that allow to detect cancer phase mutation. Aim: The purpose of this dissertation is to evaluate the knowledge of genetic predispositions to cancer among the citizens of Swietokrzyskie Voivodeship. Material and methodology: The research has been carried out on 93 people living in the Swietokrzyskie Voivodeship aged between 18-75. The chosen measurement method was a survey testing the knowledge of genetic predispositions to cancer. Results: Among the questioned the majority were women (61%). The average age was 48 among men and 33 among women. The majority of questioned (60%) were living in a city. The level of education was diverse. Even tough, some of the questioned are or were suffering from cancer (28% of women and 53% of men) or someone in their close relation is or has suffered from cancer (49% in case of women and 64% among men) they do not have the knowledge of the genetic predispositions to cancer. Conclusions: The awareness of questioned about the genetic predispositions to cancer inheritance or the possibility of using genetic tests to detect the cancer is insufficient. Regarding to the fact that approximately 30% of cancers have genetic conditions, providing complete and structured knowledge seems to be an important element of health education, because early detection increases the chance of recovering. Keywords: cancers, genetic predisposition, hereditary cancer.